Importance of Foreign Language for Non-Native Students - Maftuna Shermatovna Omonova (Open Academia, 2023)
The purpose of this article is to clarify why learning a foreign language is important not only for linguists, but also for representatives of other fields. Scientific articles and monographs written on this topic were used as a scientific source for writing a scientific article. The importance of a foreign language is the object of study of this article, and why it is important for representatives of other fields is the subject of the article.